Efektivitas Model Pembelajaran Kooperatif Tipe Teams-Games-Tournament (TGT) Terhadap Sikap Sosial Siswa Kelas V SDN 1 Padangbulia Tahun Ajaran 2019/2020 - Made Adi Nugraha Tristaningrat; Komang Trisna Mahartini; Luh Novi Kusuma Dewi (STAHN Mpu Kuturan Singaraja, 2020)
This research aims to provide the effectiveness of the use of innovative learning in the social attitudes of students. Education is one of the components that contribute to the success of nation development. The most notable improvement in student activity during the learning process by using the Teams-Games-Tournament (TGT) cooperative learning model has increased The most notable improvement is that the social skills of grade V students at SD N 1 Padangbulia are shown in the observation results of students ' social skills towards classroom learning. The most prominent aspect of social skills is the aspect of collaborating with others and the aspect of caring. Keywords: cooperative, social, TGT